Comparison of dynamic response and maximum principal strain of diagnosed concussion in professional men's rugby league. (December 2022) - Ignacy, Talia; Post, Andrew; Gardner, Andrew J; Gilchrist, Michael D; Hoshizaki, Thomas Blaine
Rugby league has been identified as a contact sport with a high incidence of concussion. Research has been conducted to describe incidence and mechanisms of concussion in rugby league, however the risks associated with injury events (shoulder, hip, head to head) are unknown. The purpose of this study was to describe the common injury events leading to concussion in the National Rugby League and compare these events through analysis of dynamic response and brain tissue deformation. Twenty-seven impact videos of concussive injuries were physically reconstructed to obtain linear and rotational accelerations of the head. Dynamic response data were input into the University College Dublin Brain Trauma Model (UCDBTM) to calculate maximum principal strain (MPS). Head-to-head events produced a short duration event with an average peak linear and peak rotational acceleration of 205 g and 15, 890 rad/s 2, respectively, which were significantly greater than the longer duration hip-to-head (24.7 g and 2650 rad/s 2 ) and shoulder-to-head (24.2 g and 3280 rad/s 2 ) impacts. There were no differences in MPS between events. These results suggest that risk of strain to the brain may be produced by short and long duration acceleration events. Thus, both of these accelerations need to be accounted for in the development of improved head and body protection in rugby. In addition, this data demonstrates that these events cause a risk of concussion requiring efforts to limit or modify how energy is transferred to the head.